EFEKTIVITAS CUCI TANGAN MENGGUNAKAN SABUN SEBAGAI UPAYA PENCEGAHAN INFEKSI : TINJAUAN LITERATUR - Rendi Ariyanto Sinanto; Sitti Nur Djannah (Jurnal Kesehatan Karya Husada, 2020)
Indonesia is a country that aggressively promotes public health, the government has launched a program of washing hands with soap that is useful to improve hygiene so as to avoid disease. The purpose of this study is to find out how effective hand washing with soap / hand hygiene is in preventing infection. This research was conducted on 3 to 10 July 2020 using the literature review method. The study was conducted on an article on http://garuda.ristekdikti.go.id published between 2015 and 2020. The results showed that washing hands with soap / hand hygiene in preventing infections was very effective, it was proven that washing hands with soap can reduce the risk of infection. Washing hands with soap is a pillar of community-based total sanitation, which includes six steps of hand washing. The use of hand sanitizers and soaps can reduce the number of bacterial colonies on the hands, and sanitizers that contain 70% alcohol are very effective in reducing the number of germs. Keywords: CTPS, hand washing, hand hygiene, prevention of infection.